Bovine Genome Database: new tools for gleaning function from the Bos taurus genome. Issue Volume 44:Issue D1(2016) (19th October 2015) - Elsik, Christine G.; Unni, Deepak R.; Diesh, Colin M.; Tayal, Aditi; Emery, Marianne L.; Nguyen, Hung N.; Hagen, Darren E.
Abstract: We report an update of the Bovine Genome Database (BGD) (http://BovineGenome.org ). The goal of BGD is to support bovine genomics research by providing genome annotation and data mining tools. We have developed new genome and annotation browsers using JBrowse and WebApollo for two Bos taurus genome assemblies, the reference genome assembly (UMD3.1.1) and the alternate genome assembly (Btau_4.6.1). Annotation tools have been customized to highlight priority genes for annotation, and to aid annotators in selecting gene evidence tracks from 91 tissue specific RNAseq datasets. We have also developed BovineMine, based on the InterMine data warehousing system, to integrate the bovine genome, annotation, QTL, SNP and expression data with external sources of orthology, gene ontology, gene interaction and pathway information. BovineMine provides powerful query building tools, as well as customized query templates, and allows users to analyze and download genome-wide datasets. With BovineMine, bovine researchers can use orthology to leverage the curated gene pathways of model organisms, such as human, mouse and rat. BovineMine will be especially useful for gene ontology and pathway analyses in conjunction with GWAS and QTL studies.